PENATAAN UMKM INDONESIA DI ERA DIGITAL YANG BERKEMANFAATAN HUKUM: PERBANDINGAN DENGAN TIONGKOK - Hetharie, Yosia; Ikhwansyah, Isis; Rahmawati, Ema (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The legal empowerment of Micro, Small, and Medium Enterprises (MSMEs) involves strategic policies aimed at enhancing the resilience and competitiveness of the MSME sector within a national legal framework. This encompasses aspects such as licensing, regulatory compliance, capacity building, market access, technological integration, financing mechanisms, and institutional collaboration among the government, private sector, and civil society. In the era of digital transformation, many Indonesian MSME owners face significant challenges due to limited capacity to adapt to rapid technological advancements, hindering their legal and commercial development. This research adopts a normative juridical method with a comparative legal approach, utilizing literature-based analysis to examine regulatory frameworks and institutional practices. As a contribution to strengthening the legal empowerment framework for MSMEs in Indonesia, this article offers a novel perspective by proposing a hybrid legal empowerment model that integrates Indonesia’s normative and principle-based legal tradition with a pragmatic, centralized governance approach as exemplified by China. It argues that legal empowerment for Indonesian MSMEs in the digital era cannot rely solely on deregulation or administrative simplification. Rather, a more comprehensive strategy is required—one that includes state-led legal facilitation, community-based digital legal literacy initiatives, and institutional redesign that systematically embeds MSMEs into the broader legal development agenda. This integrated model is proposed as a forward-looking framework to bridge Indonesia’s legal empowerment gap and to promote inclusive and sustainable growth of MSMEs within the digital economy.